If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = 5x + 10 Reorder the terms: -6 + 7x = 5x + 10 Reorder the terms: -6 + 7x = 10 + 5x Solving -6 + 7x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 7x + -5x = 10 + 5x + -5x Combine like terms: 7x + -5x = 2x -6 + 2x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + 2x = 10 + 0 -6 + 2x = 10 Add '6' to each side of the equation. -6 + 6 + 2x = 10 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 10 + 6 2x = 10 + 6 Combine like terms: 10 + 6 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 2p^2-2p+1-1=0 | | 14+2x=5x+5 | | 8x+10=3x+20 | | 11w+26=125 | | 20=9x-7 | | 6x^3-38x^2+12x= | | 24-2x=4x | | 4x^2+7x-2= | | 27y+15+8y-8=29 | | 3x^2-48x+39=0 | | 4x^2+17x-2= | | -2(-7n+4)+9=-13 | | 5+y/8=3 | | n-=3n | | 5s-4=11 | | 7x^2-55x-8= | | -6x^2+x+15=0 | | 3x^2+30x+75= | | 28+4F=64 | | -7=w+29 | | 8x^2-14x+5= | | 8x^2-10x-12= | | 7x^2+4x-3= | | 2x^2+24x+10=0 | | (2b^2-4b^3+6)+(-5b^4+2b^2+6-1)= | | 36x^2-16= | | 24x^2+11x+1= | | x^2-16x-36= | | 6x^2+4x= | | 5n^2+29n-22=0 | | C^4-17c^2+16=0 | | 2z-31=92+24 |